Implications of Islamic Inheritance Law for the Ownership of Assets and Management of Family Wealth: An Indonesian Perspective - Dwi Siyamsih (PT. Anagata Sembagi Education, 2024)
The implementation of Islamic inheritance law in Indonesia faces complex challenges, particularly in the management of family wealth. Despite a strong legal foundation, practices often diverge due to various economic, social, and cultural factors. Factors such as local traditions, diverse religious understandings, and economic conditions influence the application of Islamic inheritance law. This research aims to delve into the implications of Islamic inheritance law on property ownership and family wealth management in Indonesia. Using a qualitative approach, including literature study and in-depth interviews, the study will analyze factors affecting the implementation of Islamic inheritance law. Thematic analysis will identify patterns and relationships, ensuring a comprehensive understanding. Data validation will ensure reliability. The research intends to contribute to policy development by providing insights into Islamic inheritance law's practical implications, fostering a better understanding of Islamic principles and ensuring fairness in inheritance distribution and wealth management.